NaFePO4 Cathode Prepared from The Caustic Fusion of A Mix Ilmenite-Hematite Followed by Cyclic Voltammetry for Na Insertion - Fitria Rahmawati; Dwi Aman Nur Romadhona; Syulfi Faiz (The Journal of Pure and Applied Chemistry Research, 2020)
Research to prepare NaFePO4 cathode material from iron sand was conducted. The iron sand consists of ilmenite FeTiO3 and hematite Fe2O3. A caustic fusion method used to precipitate iron as Fe(OH)3 and it increased Fe content up to 94.71 %. Phosphate precipitation successfully produced trigonal FePO4 and monoclinic FePO4 comply with ICSD#412736 and ICSD#281079. The prepared-FePO4 was then used as a precursor for Na insertion by applying cyclic voltammetry mode within 2.0 – 4.0 V with 0.05 mVs-1 of the scan rate. It produced orthorhombic olivine NaFePO4 and a secondary phase of orthorhombic Na0.7FePO4. Impedance analysis at 20 Hz – 5 MHz found that the material provided a semicircle at 100 Hz peak point, indicating electrode-bulk interface with a resistance value of 1735W, comparable to the electrical conductivity of 5.36 x 10-6 Scm-1. Even though the conductivity value is quite lower than NaFePO4 prepared from a commercial FePO4 that has been conducted in our previous research, however the electrical conductivity still reliable for cathode.